Analyzing COBIT 5 IT Audit Framework Implementation using AHP Methodology - Mutiara AB; - Prihandoko; Prasetyo E; Widya C (Politeknik Negeri Padang, 2017)
COBIT has been known as the best practice standard in IT Governance, both in management or evaluated of the IT utilization. The role of IT Audit framework to evaluate the benefits of Information Technology in an enterprise either its gain benefits or fail in order to achieved the business objective. In Indonesia, most organization has been implemented the IT as their main support of process business, and deliberately conduct the evaluation of the implementation used some IT Audit framework such as ITIL, TOGAF, COBIT and other Government rule. Those frameworks have been known as an IT governance framework, most of organizations are choosing COBIT and ITIL due to the internal control issues. Therefore, this research will be focus on COBIT 5 utilization as an IT audit frameworks, a comparison also will be done between the COBIT 5 and ITIL. The comprehensive parameters in COBIT 5 which provides 5 category process in two domain, management and control will be the variables of prioritizing process among them for each object. This paper will analyze the use of those parameters for some selected organization and prioritize them using the Analytical Hierarchy Process (AHP) methodology that will lead to create a new model of IT Audit frameworks based on the user requirement and opinion. the analyzing process the implementation of COBIT 5 framework in some organizations, and priorities the preferred attributes of COBIT 5 that very likely and suitable to the culture and needs of user in Indonesia using AHP Methodology, and create the best qualified model of IT Audit that fit with the requirements of the organizations especially for Indonesia organizations and companies.